An Evaluation of a Parent Implemented In Situ Pedestrian Safety Skills Intervention for Individuals with Autism. - Harriage, Bethany; Blair, Kwang-Sun; Miltenberger, Raymond (Journal of Autism & Developmental Disorders, 2016)
This study evaluated an in situ pedestrian safety skills intervention for three individuals with autism , as implemented by their parents. Specifically, this study examined the utility of behavioral skills training (BST) in helping parents implement most-to-least prompting procedures in training their children to use pedestrian safety skills in community settings. A multiple baseline design across participants was used to assess parent implementation of in situ pedestrian safety skills training as well as the correct use of safety skills independently by the participating individuals with autism. Results indicated that parents implemented in situ, most-to-least prompting procedures with high levels of accuracy across street locations during intervention and fading of BST. All child participants significantly improved their pedestrian safety skills during intervention across all natural street settings. For all three participants, the acquired skills were maintained above baseline levels at 1-month follow-up.